Hubungan Asupan Zat Gizi dengan Berat Lahir Bayi (Studi pada Ibu Hamil Anemia di Puskesmas Bulu, Temanggung, Jawa Tengah Tahun 2017) - Hani Novita Sari Pratiwi; M. Zen Rahfludin; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2017)
Anaemic pregnancy is a condition of the mother with hemoglobin level <11 gr% . The outcome of anaemic during pregnancy is increased risk of low birth weight baby. Low birth weight is caused by lack of nutritional intake during pregnancy. The purpose of this research was to analyze the correlation of nutritional intake with baby birth weight in anaemic pregnant women in Bulu Health Center, Temanggung, Central Java. This research was a quantitative analytical approach with cross sectional design. Samples of this research were 45 pregnant women who met the inclusion criteria, but there was one pregnant woman who experienced stillbirth, so the total samples were 44. Sampling technique was using purposive sampling.  Data was collected using FFQ – Semi Quantitative and analyzed using Rank Spearman and Pearson Product Moment. Results of this research showed that Level of Energy consumption was classified as low (45,5%). Level of Protein consumption was classified as very low (47,7%). Level of Carbohydrate consumption was classified as deficit (59,1%) and fat consumption was classfied as deficit (50%). Intake of vitamin D, and calcium were classified as low (95,5%). Intake of folic acid, iron and zinc were classified as low (100%). Result of the statistical trials showed that there were no correlation between all the nutritional intake with baby birth weight in anaemic pregnant women. This research recommended pregnant women to increase nutritional intake, in order to fulfill their nutritional needs. For further research, it was needed to analyze physical activities and other factors which correlate with baby birth weight.